2018
DOI: 10.1016/j.oraloncology.2018.01.024
|View full text |Cite
|
Sign up to set email alerts
|

CD70 as a target for chimeric antigen receptor T cells in head and neck squamous cell carcinoma

Abstract: CD70-specific CAR-T cells specifically recognized and efficiently eliminated CD70-positive HNSCC cells. This study provides the basis for further investigation into CD70 and other CAR-T targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…Although numerous TAAs have been detected in HNSCC, the current literature on CAR‐T treatments report those targeting CD70 and human epidermal growth receptor factor 2 (Her2) . Therefore, it is important to broaden the HNSCC‐specific targets of CAR‐T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous TAAs have been detected in HNSCC, the current literature on CAR‐T treatments report those targeting CD70 and human epidermal growth receptor factor 2 (Her2) . Therefore, it is important to broaden the HNSCC‐specific targets of CAR‐T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, synthetic chimeric antigen receptor (CAR)‐T cell therapy has encouraging therapeutic potential in HNSCCs and hematological cancers 128–130 . A previous study identified nine overexpressed genes on the surface of HNSCCs as potential targets for CAR‐T cell therapy, 128 but only a few targeted antigens have shown favorable results. Preclinical and clinical data on HER2‐specific, CD70‐specific, and T4 (T1E28ζ/4αβ) CAR‐T cell therapy on HNSCCs demonstrate potent antitumor activity, but the risk of on‐target off‐tumor toxicity remains a challenge to overcome 128,129,131 .…”
Section: Current and Future Immunotherapies In Hnsccmentioning
confidence: 99%
“…A previous study identified nine overexpressed genes on the surface of HNSCCs as potential targets for CAR‐T cell therapy, 128 but only a few targeted antigens have shown favorable results. Preclinical and clinical data on HER2‐specific, CD70‐specific, and T4 (T1E28ζ/4αβ) CAR‐T cell therapy on HNSCCs demonstrate potent antitumor activity, but the risk of on‐target off‐tumor toxicity remains a challenge to overcome 128,129,131 . T4 + CAR T‐cells are retrovirally transduced to coexpress (a) T1E28ζ, a CAR coupling ErbB ligand derived from EGF and TGFα to a fused CD28/CD3ζ endodomain; and (b) 4αβ, a chimeric cytokine receptor containing the IL‐4Rα ectodomain coupled to the IL‐2Rβ endodomain 131 …”
Section: Current and Future Immunotherapies In Hnsccmentioning
confidence: 99%
“…The aberrant expression of CD70 has been detected on hematological malignancies and also on some solid tumors, such as osteosarcoma, renal cell carcinoma, thymic carcinoma, nasopharyngeal carcinoma and glioblastoma 10 - 14 . Several reports have also provided the evidence suggesting the therapeutic potential of CD70 targeted CAR-T cell 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%